Um estudo dos mapas conceituais como instrumento de auto avaliação em ciências: concepção de alunos/as do ensino fundamental I - Silva, Luzia Marinalva da (2014)
This study focuses on assessment practices in Science education in elementary school, and the main objective is to analyze the students´ conception of alternative assessment models, especially self-assessment, based on the principles of Ausubel´s theory on Meaningful Verbal Learning. Self-assessment, in this case, happens when the students elaborate Concept maps, and use them as instruments to facilitate learning. The field work focused on the students´ conception of their active participation in the assessment process regarding the content of Mechanic Energy in Natural Sciences. In order to carry out this research, various strategies were used: explanatory class, elaboration of Concept Maps, handling of the learning object, and interviews. The research was supported by the theoretical presuppositions that point to the need to change the scientific work in school and the formative concept of the assessments as a possibility to improve learning, through the Theory of Meaningful Verbal Learning and through the use of the learning object as the pedagogical tendency that facilitates meaningful learning. The methodology applied is an explorative, qualitative approach with field strategies, both in relation to the place where the data was collected and in relation to the cross temporary sources of information. During the collection of data, Concept maps were elaborated by the students and interviews were carried out in order to gather the students´ conceptions of the assessment process. The results show that Concept maps, used as assessment tools, involve the students in an active and meaningful way in the assessment process, which opens possibilities to progress beyond the traditional assessment model based on memorizing information.